2022
DOI: 10.1177/02841851221093764
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of simultaneous localization of multiple lung nodules using coils and risk factors for pneumothorax: a retrospective study

Abstract: Background Localization of lung nodule before video-assisted thoracoscopic surgery (VATS) can help the surgeon to quickly and accurately find the lesion during surgery. Purpose To evaluate the safety and effectiveness of using coils to simultaneously locate multiple lung nodules under computed tomography guidance and to clarify the risk factors for pneumothorax. Material and Methods From January 2020 to December 2020, 61 patients underwent simultaneous localization of multiple lung nodules (Group A) and 120 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In the present study, demographics, pulmonary nodules, and technical factors were found to have no significant impact on pneumothorax. In support of this, some studies have indicated that frequency is the only significant independent risk factor for pneumothorax ( 19 - 21 ). However, this study only considered patients with a single nodule, and excluded the possible impact of multiple injections.…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, demographics, pulmonary nodules, and technical factors were found to have no significant impact on pneumothorax. In support of this, some studies have indicated that frequency is the only significant independent risk factor for pneumothorax ( 19 - 21 ). However, this study only considered patients with a single nodule, and excluded the possible impact of multiple injections.…”
Section: Discussionmentioning
confidence: 84%
“…Our results are consistent with these previous findings; however, we excluded patients with multiple nodules to reduce the potential interference from the simultaneous analysis of single and multiple nodule cases. This approach might address the differing complication rates for single and multiple nodules in previous studies that may have influenced multivariate regression analysis outcomes [9,12]. Furthermore, our study consistently used PBV dye for localization, whereas a previous study used various methods, such as hook wires, for deeper nodules [18].…”
Section: Discussionmentioning
confidence: 99%
“…Because complication rates differ between multiple and single nodules and because most patients in our cohort had a single nodule, we used single nodules as the standard for analysis [9,12]. The inclusion criteria were based on those used in previous studies based on the research of Kong et al assessing individuals with a single lung nodule [11]: (a) being 18-80 years old; (b) having a single small lung nodule measuring 5-15 mm in diameter that was diagnosed by at least two radiologists as being potentially malignant; (c) having no imaging evidence of emphysema, pulmonary hypertension, or pulmonary fibrosis; (d) having intraoperative and postoperative pathological results; (e) having no obvious vasculitis, bullae, or other important tissues or structures in the needle puncture path; and (f) having normal coagulation function.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations